Cyberlaundering sebagai Evolusi Pencucian Uang: Keterbatasan Konsep Pertanggungjawaban Pidana di Era Digital - Muhammad Imam Fakhri; Muhammad Kamal Hidjaz; Andi Istiqlaal Assaad (HORIZON PUBLIC LEGAL STUDIES, 2025)
This study aims to analyze the legal regulation of money laundering through digital technology (cyberlaundering) in the Indonesian legal system, as well as the forms and basis of criminal liability for perpetrators. This study uses a normative legal research method with a legislative, conceptual, case, and comparative approach. The legal materials used include primary, secondary, and tertiary legal materials obtained through literature and documentation studies, which are then analyzed qualitatively to interpret legal norms related to cyberlaundering. The results of the study show that cyberlaundering is not specifically regulated in any single regulation, but can be prosecuted under criminal provisions on money laundering and technology-neutral electronic transaction regulations. The Financial Transaction Reports and Analysis Center plays an important role in detecting suspicious digital-based financial transactions. Criminal liability can be imposed on individuals and corporations with the support of electronic evidence. However, there are still weaknesses related to the classification of digital assets, procedures for seizing virtual assets, and the regulation of technological entities such as smart contracts and DAOs, so legal reforms that are more adaptive to developments in digital technology are needed.